Using the Myers-Briggs Type Indicator to Study Managers: A Literature Review and Research Agenda - Gardner, William L.; Martinko, Mark J. (Journal of Management, 1996)
This paper provides a review of research into the relationships between psychological types, as measured by the Myers-Briggs Type Indicator (MBTI), and managerial attributes, behaviors and effectiveness. The literature review includes an examination of the psychometric properties of the MBTI and the contributions and limitations of research on psychological types. Next, key findings are discussed and used to advance propositions that relate psychological type to diverse topics such as risk tolerance, problem solving, information systems design, conflict management and leadership. We conclude with a research agenda that advocates: (I) the exploration of potential psychometric refinements of the MBTI, (2) more rigorous research designs, and (3) a broadening of the scope of managerial research into type.